(untitled) (Revista Universitaria del Caribe, 2025)
This is a comparative analysis study that highlights the application of math games specifically developed for Spanish and USA inclusive classes involving students suffering from learning disability and other special needs. This study has been done on information collected from 24 schools, 12 schools in each country. Findings indicate that American educators incorporate games based upon principles of Universal Design for Learning (UDL), individualized education programs (IEP), and differentiated instruction. This is increasingly formalized, backed by teacher training, and built into curriculum goals. Spanish educators, while positive about engaging in game-playing activities, resort to game-playing to a lesser extent and place more emphasis on improvisation, due to limited training availability and a more formalized curriculum. Both sets of students enjoy the games, however, only the U.S. students demonstrate improvement in school performance because of modified games. The Spanish schools prefer using games more for motivation than for instructional methods, making more accommodations for differing needs. Cultural preferences for handling differentiation and disability affect the implementation process because the U.S. culture embraces independence and autonomy, while the Spanish culture values unity and standardization. It is found that there is immense potential in modified versions of games to be included if they are developed according to their requirements. It suggests more professional development, openness of curriculum, and culturally responsive practice while modifying. By citing its limitations and advantages at the national level, it gives a glimpse of the potential of classrooms of the future.